FUNCTIONS AND GROUNDS OF ECONOMIC AND LEGAL RESPONSIBILITY: ADMINISTRATIVE DIMENSION - Матвійчук, Анатолій Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Aim: to determine the legal models of the specific features of economic and legal liability as an integral part of economic activity. To propose effective mechanisms of legal support for bringing business entities to legal entities. To offer author’s conceptions of the functioning of economic responsibility in the system of law. Methods: the study was conducted using classical methods of scientific knowledge. Using the method of analysis, the system elements of economic responsibility are disclosed. The method of synthesis considers the conceptual aspects of economic responsibility. Results: according to the results of the research, author’s elements of the concept of economic responsibility are proposed. Identified and disclosed components of the legal aspect of economic responsibility. It is necessary to draw the following conclusions, first: under a legal basis, understand the legal document characterizing a certain behavior of the subject of economic activity as unlawful and foresees for her the form and amount of liability, namely: law and contract. This ground consists of four elements - the terms of economic legal liability: a) the fact of economic offense, that is, violation of the law, the terms of the contract, government contract, etc., resulting in damages or other damage to the property rights and interests of the victim (creditor). An economic violation is a consequence of the unlawful conduct of the economic offender. This may be an act or omission that violates a legal norm, a scheduled task, a contract, etc.; b) losses caused by violations of economic obligations or established requirements for the conduct of economic activity; c) the causal relationship between the wrongful conduct of the offender and the damage inflicted by the victim. This should be a cause-and-effect connection, where the unlawful act or inaction is an objective cause of such an effect as the damage or other damage suffered by the victim (creditor); d) the fault of the offender - a participant in economic relations. Secondly: it is a negative subjective attitude of the offender to the rights and legitimate interests of the victim. It should be borne in mind the reservation of the law according to which a participant in economic relations is responsible for failure or improper performance of an economic obligation or violation of the rules for the conduct of economic activity, unless it is proved that he has used all the measures dependent on him to prevent the economic offense. Unless otherwise provided by law or agreement, an entity is liable for economic violation of an economic obligation if it does not prove that the proper fulfillment of the obligation was impossible due to the force majeure, that is, the extraordinary and unavoidable circumstances of the data conditions of economic activity. Not considered such circumstances, in particular, violation of obligations by contractors of the offender, absence of the necessary goods for the fulfillment of obligations on the market, absence of necessary funds from the debtor (Part 2 of Article 218 of the Civil Code). The author proposes to consider actual life situations, which are characterized by law or contract as unlawful. First of all, the actual grounds for economic liability should be distinguished by subject and object.